2022
DOI: 10.1021/acs.biomac.2c01187
|View full text |Cite
|
Sign up to set email alerts
|

Shape Matters: Highly Selective Antimicrobial Bottle Brush Copolymers via a One-Pot RAFT Polymerization Approach

Abstract: The one-pot synthesis of antimicrobial bottle brush copolymers is presented. Reversible addition–fragmentation chain-transfer (RAFT) polymerization is used for the production of the polymeric backbone, as well as for the grafts, which were installed using a grafting-from approach. A combination of N-isopropyl acrylamide and a Boc-protected primary amine-containing acrylamide was used in different compositions. After deprotection, polymers featuring different charge densities were obtained in both linear and bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…41) Gleichsam untersuchten Hartlieb und Team die Struktur-Eigenschaftsbeziehungen antimikrobieller Polymerbürsten. 42) Ebenfalls antimikrobielle Eigenschaften wiesen die Polyethersulfonmembranen auf, die Börner und Mitarbeitende entworfen und mit Photosensibilisatoren ausgerüstet hatten. 43) Fortschritte in der Synthese biomedizinisch wirksamer Makromoleküle erzielten Hartmann, Snyder und Hoffmann: Ihnen gelang die Festphasensynthese von sulfatierten Glykomakromolekülen als Analoga für biologisch aktive sulfatierte Glykosaminoglykane.…”
Section: Verkapseln Und Freisetzenunclassified
“…41) Gleichsam untersuchten Hartlieb und Team die Struktur-Eigenschaftsbeziehungen antimikrobieller Polymerbürsten. 42) Ebenfalls antimikrobielle Eigenschaften wiesen die Polyethersulfonmembranen auf, die Börner und Mitarbeitende entworfen und mit Photosensibilisatoren ausgerüstet hatten. 43) Fortschritte in der Synthese biomedizinisch wirksamer Makromoleküle erzielten Hartmann, Snyder und Hoffmann: Ihnen gelang die Festphasensynthese von sulfatierten Glykomakromolekülen als Analoga für biologisch aktive sulfatierte Glykosaminoglykane.…”
Section: Verkapseln Und Freisetzenunclassified
“…Furthermore, establishing a robust supramolecular platform would allow a versatile variation of attached polymers, while the elongated shape of the SPBs remains unaffected. [65,66] Moreover, such a systematic study allows cross-correlations with other systems and might lead to more general understanding on the influence of the polymer architecture on the final morphology. [12,[67][68][69] In this study, we therefore attached polymers of different length and side chain size to the established benzene trisurea (BTU) and benzene tris(phenylalanine) (BTP, formerly also called benzene trispeptide) core motifs to provide fundamental structure-property relations between the sterical demand of the attached polymers and the preservation of fiber formation in these promising supramolecular building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…and Laroque et al 25 . Bottlebrush copolymers have also demonstrated increased activity compared to that of the linear form 26–28 …”
Section: Introductionmentioning
confidence: 99%
“…Even less employed, star polymers may present extended antimicrobial activity compared with their linear counterparts, 23 as demonstrated by Lam et al 24 and Laroque et al 25 Bottlebrush copolymers have also demonstrated increased activity compared to that of the linear form. [26][27][28] Star-shaped polymers prepared by reversible deactivation radical polymerization techniques are typically achieved using the core-first or arm-first methods. 29 Core-first methods use a multifunctional core from which the linear arms will grow, whereas by the arm-first method, the linear arms are obtained in the first step and then a bifunctional monomer, a crosslinker, is used to react with the linear chains and subsequently with other crosslinker molecules, resulting in a spherical polymeric topology.…”
Section: Introductionmentioning
confidence: 99%